Posology and Serum-/Xeno-Free Engineered Adipose Stromal Cells Cell Sheets - Ochiai, Jun; Villanueva, Larakaye; Niihara, Hope; Niihara, Yutaka; Oliva, Joan (Frontiers in Cell and Developmental Biology, 2022)
Well characterized adipose stem cells and chemically defined culture media are important factors to control the production of the cell sheet, used in translational medicine. In this study, we have developed and engineered multilayer adipose stem cells cell sheets (ASCCSs) using chemically defined/serum free culture media: undifferentiated or differentiated into osteoblasts and chondrocytes. In addition, using the cell sheet transmittance we estimated the number of cells per cell sheet. Undifferentiated ASCCSs were engineered in 10 days, using a serum free, xeno-free culture media. They were CD29+, CD73+, CD90+, CD105+, HLA-A+, HLA-DR-. Differentiated ASCCS into chondrocyte and osteoblast were also engineered using chemically defined and animal free culture media, in only 14 days. The addition of ROCK inhibitor improved the chondrocyte cell sheet engineering. The decrease of cell sheets transmittance rate was higher for the osteoblast cell sheets due to the intracellular Ca2+ accumulation. Estimation of cell number per cell sheet was estimated with the transmittance, which will provide an important information for the cell sheet posology. In conclusion, three types of ASCCS were engineered using serum-free, xeno-free culture media, expressing their specific markers. Their transmittance measurement allowed to estimate the number of cells per cell sheets, with a non-invasive methodology.